Improved modelling of the freshwater provisioning ecosystem service in water scarce river basins. (August 2017) - Momblanch, Andrea; Paredes-Arquiola, Javier; Andreu, Joaquín
Abstract : Freshwater provisioning by the landscape contributes to human well-being through water use for drinking, irrigation and other purposes. The assessment of this ecosystem service involves the quantification of water resources and the valuation of water use benefits. Models especially designed to assess ecosystem services can be used. However, they have limitations in representing the delivery of the service in water scarce river basins where water management and the temporal variability of water resource and its use are key aspects to consider. Integrating water resources management tools represents a good alternative to ecosystem services models in these river basins. We propose a modelling framework that links a rainfall-runoff model and a water allocation model which allow accounting for the specific requirements of water scarce river basins. Moreover, we develop a water tracer which rebounds the value of the service from beneficiaries to water sources, allowing the spatial mapping of the service. Highlights: The freshwater provisioning ecosystem service is influenced by water management. Water resources management models capture this better than ecosystem service tools. We link hydrologic, water allocation and water quality models to assess the service. They fit temporal and spatial details of ecological processes and water management.